Hubungan Kepatuhan Minum Obat terhadap Kualitas Hidup Pasien TB Paru di Rumah Sakit Budiasih - Mia Meilani; Candra Junaedi; Fajrin Noviyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis, which generally attacks the lungs, although it can affect other organs. The World Health Organization (WHO) identifies TB as a leading cause of death worldwide, with millions of new cases each year. A crucial factor in TB treatment is patient compliance with treatment, as irregular treatment can lead to drug resistance and weaken the patient's condition. This study aims to determine the relationship between medication adherence and quality of life of pulmonary TB patients at Budiasih Hospital. The method used is an observational study with a cross-sectional approach. The study population was pulmonary TB patients, with a sample consisting of patients who met the inclusion and exclusion criteria. The questionnaires used included the MMAS-8 to measure compliance and the WHOQOL-BREF 1996 to measure quality of life. Data analysis was performed using the chi-square test to examine the relationship between variables. The second variable is said to have a significant relationship if the p-value is less than 0.05. The results showed that the fulfillment of drinking water for pulmonary TB patients was categorized as high at 54.0%, and the quality of life of most pulmonary TB patients was categorized as moderate at 69.8%. The analysis also revealed a significant relationship between medication adherence and the quality of life of pulmonary TB patients at Budiasih Hospital, with a p value of 0.000 (p<0.05). This study provides important insights into the importance of implementing treatment to improve the quality of life for pulmonary TB patients. In addition, this study also showed that although the majority of patients had a good level of medication fulfillment, the majority of patients still experienced a moderate quality of life.